Efficiency Improvement by Simulation Technique in the Parcel Service Company - Klomjit, Prachuab; Anurattananon, Chanpen; Chatmuangpak, Alongkorn; Amaluk, Amnaht (Science & Technology Asia, 2020)
The objective of this research is to improve the efficiency of the distributed system of a partner’s product in a parcel service company by simulation technique. This research includes the solution of 3 problems: a queueing of products problem, a duplicated work processes problem and an unsystematic working area problem. The theories that apply are simulation technique (ProModel), method study, goodness of fit test, ECRS method and material handling. The queueing of products problem and duplicated work processes problem were solved by installing a belt conveyor for sorting that combined the zone sorting process and distribution center sorting process. The unsystematic working area problem was solved by arranging the working area clearly to make product flow more linear and reduce distances. All of the solutions and the current system were created as models in ProModel. The results after improving the queueing of products problem and duplicated work processes problem are increased output about 2,530 pieces per day from the original and decreased queueing time for 49.23% from the original, unsystematic working area problem solving increase output about 1,332 pieces per day from the original and decrease queueing time for 29.41% from the original.